Whole exome sequencing identifies a mutation for a novel form of corneal intraepithelial dyskeratosis. Issue 4 (24th January 2013) - Soler, Vincent José; Tran-Viet, Khanh-Nhat; Galiacy, Stéphane D; Limviphuvadh, Vachiranee; Klemm, Thomas Patrick; St Germain, Elizabeth; Fournié, Pierre R; Guillaud, Céline; Maurer-Stroh, Sebastian; Hawthorne, Felicia; Suarez, Cyrielle; Kantelip, Bernadette; et al.
Abstract : Background: Corneal intraepithelial dyskeratosis is an extremely rare condition. The classical form, affecting Native American Haliwa-Saponi tribe members, is called hereditary benign intraepithelial dyskeratosis (HBID). Herein, we present a new form of corneal intraepithelial dyskeratosis for which we identified the causative gene by using deep sequencing technology. Methods and results: A seven member Caucasian French family with two corneal intraepithelial dyskeratosis affected individuals (6-year-old proband and his mother) was ascertained. The proband presented with bilateral complete corneal opacification and dyskeratosis. Palmoplantar hyperkeratosis and laryngeal dyskeratosis were associated with the phenotype. Histopathology studies of cornea and vocal cord biopsies showed dyskeratotic keratinisation. Quantitative PCR ruled out 4q35 duplication, classically described in HBID cases. Next generation sequencing with mean coverage of 50× using the Illumina Hi Seq and whole exome capture processing was performed. Sequence reads were aligned, and screened for single nucleotide variants and insertion/deletion calls. In-house pipeline filtering analyses and comparisons with available databases were performed. A novel missense mutation M77T was discovered for the gene NLRP1 which maps to chromosome 17p13.2. This was a de novo mutation in the proband's mother, following segregation in the family, and not found in 738 control DNA samples. NLRP1 expression was determined in adult corneal epithelium. The amino acid change was found to destabilise significantly the protein structure. Conclusions: We describe a new corneal intraepithelial dyskeratosis and how we identified its causative gene. The NLRP1 gene product is implicated in inflammation, autoimmune disorders, and caspase mediated apoptosis. NLRP1 polymorphisms are associated with various diseases.